The Relationship Between Job Satisfaction and Nurse Performance in Nursing Documentation at Dr. Wahidin Sudiro Husodo Regional Hospital, Mojokerto City - Adiem Abdillah; Windu Santoso; Duwi Basuki (CV Media Inti Teknologi, 2025)
Baground: Nurse performance has become a trending issue today due to the growing public demand for high-quality services. One aspect of nurse performance that can be assessed is documentation of nursing care. Aim: The purpose of this research was to determine the relationship between job satisfaction and nurse performance in nursing documentation at Wahidin Sudirohusodo Regional Hospital, Mojokerto. Method: This research method uses a correlation analytic design with a cross-sectional approach. The population in this research is all inpatient nurses at Dr. Wahidin Sudirohusodo General Hospital, Mojokerto City, totaling 87 people. This research instrument is the Minnesota Satisfaction Questionnaire (MSQ) and a nurse performance checklist. Result: The results of the research show that almost all respondents are satisfied with their jobs, namely 66 people (93%), and almost all respondents have good performance in nursing care documentation, namely 68 people (95.8%). The results of the Spearman Rho test can be said that p-value = 0.000 with a correlation coefficient of 0.763 so that H1 is accepted. Conclusion: Nurses who are satisfied with their jobs have good performance because job satisfaction plays an important role in increasing motivation, commitment, and responsibility towards the tasks they are assigned.